2019
DOI: 10.1186/s13287-019-1503-7
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual blood-derived stem cells: toward therapeutic mechanisms, novel strategies, and future perspectives in the treatment of diseases

Abstract: Menstrual blood-derived stem cells (MenSCs) have great potential in the treatment of various diseases. As a novel type of mesenchymal stem cells (MSCs), MenSCs have attracted more interest due to their therapeutic effects in both animal models and clinical trials. Here, we described the differentiation, immunomodulation, paracrine, homing, and engraftment mechanisms of MenSCs. These include differentiation into targeting cells, immunomodulation with various immune cells, the paracrine effect on secreting cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 103 publications
1
99
0
Order By: Relevance
“…Wilson et al [71] have recently found that the administration of allogeneic MSCs for nine patients with ARDS did not lead to any particular adverse events such as cardiac arrhythmia, hypoxemia, and ventricular tachycardia. MSCs taken from menstrual blood have recently become attractive because of easy access, high rate of proliferation, and a non-invasive procedure lacking ethical issues [77][78][79]. Chen et al argue that MSCs are capable of reducing inflammatory effects and avoiding cytokine storm.…”
Section: Msc-based Therapy In Covid-19 Patientsmentioning
confidence: 99%
“…Wilson et al [71] have recently found that the administration of allogeneic MSCs for nine patients with ARDS did not lead to any particular adverse events such as cardiac arrhythmia, hypoxemia, and ventricular tachycardia. MSCs taken from menstrual blood have recently become attractive because of easy access, high rate of proliferation, and a non-invasive procedure lacking ethical issues [77][78][79]. Chen et al argue that MSCs are capable of reducing inflammatory effects and avoiding cytokine storm.…”
Section: Msc-based Therapy In Covid-19 Patientsmentioning
confidence: 99%
“…MSCs derived from menstrual blood are widely studied because of their abundant source, strong proliferation ability, low immunogenicity, and painless surgery without ethical controversy [28][29][30][31]. Thus, menstrual bloodderived MSCs have attracted increasing attention, and they have been broadly applied in basic medicine and clinical trials [32,33]. Our team has also demonstrated that menstrual blood-derived MSC transplantation is an alternative method for treating ARDS with influenza A (H7N9) infection and thereby reducing mortality relative to controls [34].…”
Section: Introductionmentioning
confidence: 97%
“…1 ). These cells are isolated from a variety of tissues like bone marrow (BM), adipose tissue, fetal liver, umbilical cord (UC), muscle, endometrial polyps, dental tissue, synovial fluid, skin, foreskin, Wharton’s jelly (WJ), placenta, dental pulp (DP), breast milk, gingiva, amnion, and menstrual blood [ 40 54 ]. MSCs are characterized as plastic adherent cells with fibroblastic morphology in culture.…”
Section: Introductionmentioning
confidence: 99%